Optical coherence tomography in the diagnosis and evolution of lupic choroidopathy. Case report - Barriga-Salaverry, Guillermo (2022)
Systemic lupus erythematosus (SLE) is an autoimmune disease that affects multiple organs including the eyes. Among the ocular manifestations of SLE is lupus choroidopathy, a rare condition but with significant visual repercussions if not treated promptly. We present the case of a 41-year-old woman who developed a lupus choroidopathy during the reduction of the dose of corticosteroid therapy for SLE, studied with retinal angiofluoresceinography and OCT for the diagnosis and follow-up of her ocular involvement. Both the dye leaks and the serous retinal detachments resolved with the treatment of high doses of prednisone but recurred twice despite the control of the underlying disease. The clinical characteristics are emphasized to allow its recognition, highlighting the use of optical coherence tomography (OCT) for its diagnosis and follow-up after treatment.